EVALUASI LAHAN UNTUK ZONASI KOMODITAS UNGGGULAN PERTANIAN KASUS KAWASAN RAWA PASANG SURUT KABUPATEN BATOLA - ., Mubekti (Jurnal Teknologi Lingkungan, 2010)
The evaluation of agricultural commodity zoning is implemented on tidal swamp area in Batola District, South Kalimantan Province . In fact, the quality of land varies from one place to the others due to the presence of limiting factors in it. Therefore a study of land suitability is essentially needed before utilizing land for cultivation. The method used in the study refers to FAO procedure and Soil Research Institute as well. A brief explanation of land resources evaluation, land suitability and commodities zoning for food crop,horticulture, and plantation crop is presented in the methodology. Then, the results of land characterization and suitability classification in Batola District are discussed, so that,more derstanding in respect to land properties and quality is derived. There are threegroups of soils is found the study area, namely peat soils, marine soils and pluviatile soils. By nature those soils have several limiting factors, i.e. drainage (flooding), acidity,sulphate potential, salinity, and low fertility. The highest grade of suitable land in Batola is only S2 (moderately suitable), and the largest area is classified as S3 (marginally suitable) for all analyzed cultivation. Since, the results of land suitability were derived then the commodities zoning were conducted. Water managing, liming, and fertilizing are definitely needed for land development and land reclamation.Key words: land evaluation, commodities zoning, GIS, agriculture